Pengaruh Daya Tarik Promosi Dan Kemudahan Penggunaan Teknologi Terhadap Loyalitas Pengguna E-Money: Pada Produk E-Money Bank Syariah Indonesia Kantor Cabang Pembantu Radial Palembang - Siti Maslahah; Hilda Hilda; Fakhrina Fakhrina (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
The purpose of this research is to determine the effect of promotional attractiveness and ease of use of technology on loyalty in using e-money (in Indonesian sharia bank e-money products at the Radial Palembang sub-branch office). This research uses primary data with a quantitative approach. The population in this study were customers of Bank Syariah Indonesia (BSI) Palembang Radial Palembang Sub-Branch who used 200 e-money products in the last 1 year. Sampling in this research used the Slovin formula, resulting in 67 customers being sampled in this research. The analytical methods used in this research are validity, reliability, classical assumption testing, multiple linear regression and hypothesis testing using IBM SPSS 26 statistical analysis. The results of this research show that the promotional attractiveness variable has a significant effect on e-money user loyalty and the ease of use of technology variable has a significant effect on e-money user loyalty.